Pathomechanism of Leukoaraiosis: A Molecular Bridge Between the Genetic, Biochemical, and Clinical Processes (a Mitochondrial Hypothesis) - Szolnoki, Zoltán (Neuromolecular medicine, 2007)
Ischemic demyelination in the white matter of the brain is a frequent clinical entity. In neuroimaging terms, it is referred to as leukoaraiosis (LA). LA can reflect a broad public health problem, which is caused by a cognitive impairment ranging from mild slowness of thinking to full-blown subcortical dementia. One-quarter of subjects aged 65 yr or over are affected by some degree of white matter changes. There are a number of genetic factors that can be associated with circulatory disturbances of the white matter of the brain. A slight chronic hypoperfusion or an endothelial dysfunction associated with unfavorable genetic variations such as methylenetetrahydrofolate reductase C677T variation and angiotensin-converting enzyme I/D polymorphism then may lead indirectly to a malfunction of the molecular cross-talk between the nucleus and the mitochondria. This results in a decrease in the production of energy in the glia cells and thereby the beginning of demyelination. From another aspect, the presence of either the apolipoprotein E 2 or 4 alleles may cause an increased vulnerability to a slight chronic hypoperfusion of the white matter by reducing the range of mechanical and chemical flexibility of the glial cytoskeleton. In consequence of the chronic hypoperfusion, the functionally damaged kinesin protein gives rise also to the disturbances of the trafficking of the myelin basic protein mRNAs in the oligodendrocytes. On the basis of the current knowledge on LA, this article suggests a hypothetical molecular bridge between the genetic, biochemical, and clinical processes.